Lepanthes elizabethae (Pleurothallidinae, Orchidaceae), a new species from Colombia - Pérez-Escobar, Oscar Alejandro; Kolanowska, Marta; Parra-Sánchez, Edicson (Phytotaxa, 2013)
With over 800 species, Lepanthes Swartz (1799: 85) is one of the largest genera in Pleurothallidinae (Orchidaceae). It ranges from southern Mexico to Bolivia and northern Brazil. A high level of endemism is observed in the Andes of Colombia and Ecuador (Pridgeon 2005). Despite the large number of species described by Luer (1986, 1994, 1996, 2009), several new Lepanthes have been described by other authors (Catling & Catling 1988, Tremblay & Ackerman 1993, Ortiz 1998, Pupulin & Bogarín 2004, Pupulin et al. 2010).